2017
DOI: 10.1007/s00213-017-4644-3
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing effect of COR659 on alcohol, sucrose, and chocolate self-administration in rats: involvement of the GABAB and cannabinoid CB1 receptors

Abstract: COR659 might exert its behavioral effects via a composite mechanism: (i) positive allosteric modulation of the GABA receptor, responsible for a large proportion of reduction of alcohol self-administration; (ii) an action at other receptor system(s), including the cannabinoid CB receptor, through which COR659 affects seeking and consumption of highly palatable foods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 64 publications
3
13
0
Order By: Relevance
“…sP rats meet all the fundamental requirements posed when defining an animal model of alcohol use disorder (AUD) (see Colombo et al, 2006;Bell et al, 2012). Notably, in relation to the aims of the present study, several previous studies indicated that alcohol self-administration and cue-induced reinstatement of alcohol seeking in sP rats were highly sensitive to positive allosteric modulation of the GABA B receptor (Maccioni et al, 2007(Maccioni et al, , 2008b(Maccioni et al, , 2009(Maccioni et al, , 2010(Maccioni et al, , 2012(Maccioni et al, , 2015(Maccioni et al, , 2017(Maccioni et al, , 2018(Maccioni et al, , 2019aLorrai et al, 2019;Ferlenghi et al, 2020).…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…sP rats meet all the fundamental requirements posed when defining an animal model of alcohol use disorder (AUD) (see Colombo et al, 2006;Bell et al, 2012). Notably, in relation to the aims of the present study, several previous studies indicated that alcohol self-administration and cue-induced reinstatement of alcohol seeking in sP rats were highly sensitive to positive allosteric modulation of the GABA B receptor (Maccioni et al, 2007(Maccioni et al, , 2008b(Maccioni et al, , 2009(Maccioni et al, , 2010(Maccioni et al, , 2012(Maccioni et al, , 2015(Maccioni et al, , 2017(Maccioni et al, , 2018(Maccioni et al, , 2019aLorrai et al, 2019;Ferlenghi et al, 2020).…”
Section: Introductionmentioning
confidence: 81%
“…The limited selectivity of KK-92A effect on alcohol selfadministration was somewhat unexpected for the following two main reasons. First, most of the GABA B PAMs tested to date have been reported to reduce alcohol self-administration with no effect on self-administration of highly palatable sucrose, saccharin, sweetened-milk, or chocolate solutions (e.g., Maccioni et al 2007Maccioni et al , 2008bMaccioni et al , 2009Maccioni et al , 2010Maccioni et al , 2012Maccioni et al , 2015Maccioni et al , 2019bLeite-Morris, 2013; see however Augier et al, 2017;Maccioni et al, 2017Maccioni et al, , 2019a. Second, treatment with the same doses of KK-92A tested in the present study resulted to be totally ineffective on operant self-administration of regular food pellets in rats (Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By binding to a different, non-competitive allosteric site on the GABA B receptor, PAMs allow endogenous GABA, binding at its original orthosteric site, to retain its potency and efficacy, reducing the risk of tolerance development and side effects [253,254]. A number of PAMs have been studied as potential pharmacotherapies for AUD, and have demonstrated reductions in alcohol-associated behaviors and ethanol self-administration in preclinical models [252,[255][256][257][258]. When directly contrasted against baclofen, a GABA B PAM had a better profile, with dose-dependent reduction of relapse-like alcohol drinking and with no signs of sedation [257].…”
Section: Asp8062mentioning
confidence: 99%